ADVERSE DRUG REACTIONS AND PHARMACOVIGILANCE IN ASU MEDICINES: A CASE STUDY AND COMPREHENSIVE REVIEW - Manuprasad K S; Harisankar K T; Amritha S Sarma (The Bioscan, 2025)
Background: Adverse Drug Reactions (ADRs) are a concern in both modern and traditional medicine, including Ayurveda, Siddha, and Unani (ASU) systems. Pharmacovigilance is essential to ensure their safe use. Case Report: A 28-year-old female with sinusitis developed an extensive erythematous rash after taking Vyoshadi Vati and Drakshasava. With no prior allergies or chronic illness, the reaction was categorized as moderate and non-serious. Symptoms resolved within 24 hours of drug discontinuation and antihistamine administration. The case was reported to the Peripheral Pharmacovigilance Centre (PPvC) via the Ayush Suraksha portal. Conclusion: This case highlights the need for robust pharmacovigilance in ASU medicine. Standardization, quality control, and systematic ADR reporting can enhance safety, credibility, and global acceptance of traditional formulations.